Spalling resistance of fiber embedded ultra-high performance concrete - Zhang, Dong (Nanyang Technological University, 2020)
Ultra-high performance concrete (UHPC), due to its dense microstructure, is highly susceptible to explosive spalling when exposed to fire, which limits its applications in building and construction sectors. It is believed that thermal stress and high vapor pressure are two main causes of spalling. To prevent spalling, one of the most widely accepted methods is addition of polymer fibers that are supposed to relieve vapor pressure by creating paths in concrete at high temperature. Although different theories have been proposed to explain the role of polymer fibers in enhancing gas permeability and reducing explosive spalling, the mechanism is still not fully understood. Moreover, there is not an appropriate method regarding optimizing fiber geometry and fiber dosage on spalling prevention. In this work, a range of analytical and microscopic characterizations were conducted to thoroughly understand the exact role of polymer fibers in the prevention of explosive spalling of UHPC. Furthermore, to better understand the interconnectivity of fibers and its effect on spalling prevention, X-ray computed tomography (CT) is employed to obtain spatial distribution of polypropylene (PP) fibers in UHPC. The connectivity of PP fibers (and thereby, percolation of fiber clusters) is calculated based on the three dimensional (3D) reconstructed model from X-ray CT results. Spalling tests and permeability measurements are also conducted on UHPC samples with different sizes of PP fibers to reaffirm the mechanism. The results suggest that thermal mismatch between embedded fibers and matrix is critical to obtaining an interconnected network of cracks in the matrix. This occurs even before melting of polymer fibers. The network of cracks is responsible for enhancing permeability, thereby reducing the susceptibility of explosive spalling of UHPC. High fiber connectivity and small inter-fiber distance are required to obtain high permeability in UHPC and thereby enhance its spalling resistance. Percolation of fiber clusters is also critical to enhancing permeability. The number of fibers that connect to percolating fiber cluster dominates the efficiency of PP fibers on spalling prevention. Thereafter, a model considering percolation of fiber/crack system is proposed based on the Kozeny-Carman equation to predict permeability of UHPC with fibers. A 3D continuum percolation model is developed to evaluate the percolation and connectivity of fiber/crack system. Finally, a semi-empirical equation is proposed to determine the geometry and dosage of PP fibers for preventing spalling of UHPC. In the last part, the usage of natural fibers as an alternative to synthetic fibers like PP fibers for preventing spalling of UHPC is explored. The effects of natural fibers on mechanical properties, hot permeability as well as spalling resistance of UHPC are investigated. Furthermore, the effects of accelerated weathering conditions on the performance of natural fibers in UHPC are also evaluated. The findings show that shrinkage of jute fibers at high temperatures enhances the permeability of UHPC and thereby, improves spalling resistance. Accelerated weathering curing affects mechanical properties of UHPC with jute fibers slightly but does not affect spalling resistance of UHPC.